2020
DOI: 10.4300/jgme-d-19-00358.1
|View full text |Cite
|
Sign up to set email alerts
|

Feedback Frequency in Competence by Design: A Quality Improvement Initiative

Abstract: Background Otolaryngology–head and neck surgery is in the first wave of residency training programs in Canada to adopt Competence by Design (CBD), a model of competency-based medical education. CBD is built on frequent, low-stakes assessments and requires an increase in the number of feedback interactions. The University of Toronto otolaryngology–head and neck surgery residents piloted the CBD model but were completing only 1 assessment every 4 weeks, which was insufficient to support CBD. Objective This proje… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 6 publications
(10 reference statements)
0
3
0
Order By: Relevance
“…19 Use of PDSA to improve medical education has been reported. Arnstead et al used PDSA cycles to improve the frequency of Competence by Design assessment in surgery residents in Canada [ 26 ]. Dunbar et al demonstrated that using PDSA cycles improved physician recognition and reporting of patient safety events [ 27 ],…”
Section: Discussionmentioning
confidence: 99%
“…19 Use of PDSA to improve medical education has been reported. Arnstead et al used PDSA cycles to improve the frequency of Competence by Design assessment in surgery residents in Canada [ 26 ]. Dunbar et al demonstrated that using PDSA cycles improved physician recognition and reporting of patient safety events [ 27 ],…”
Section: Discussionmentioning
confidence: 99%
“…PDSA has the advantage of building knowledge quickly through the efficient use of data and relying on a high 'return on failure ratio' 33 Explicit use of PDSA to improve medical education has been reported in several different contexts, including efforts to improve safety event reporting 36 or the number of resident assessments by faculty members. 37 There are also other examples where PDSAlike approaches have been used for programme development and curriculum adaptation in medical education. For example, a faculty members development programme for education scholarship at the University of Toronto used a deliberate strategy to allow programme directors to receive inputs from multiple sources to inform iterative, real-time improvements to the programme design and delivery.…”
Section: Theory Of Knowledgementioning
confidence: 99%
“…Explicit use of PDSA to improve medical education has been reported in several different contexts, including efforts to improve safety event reporting 36 or the number of resident assessments by faculty members 37 . There are also other examples where PDSA‐like approaches have been used for programme development and curriculum adaptation in medical education.…”
Section: System Of Profound Knowledge—lessons Learned From Quality Im...mentioning
confidence: 99%